The Persistence of Flavor: Past and Present Use of Wild Food Plants in Sierra Norte de Madrid, Spain - Aceituno-Mata, Laura; Tardío, Javier; Pardo-de-Santayana, Manuel (Frontiers in Sustainable Food Systems, 2021)
Despite the increasing scientific and public interest in wild food plants, their traditional knowledge is undergoing a deep cultural erosion process at a global scale. The paper assess past and present use of wild food plants in Sierra Norte de Madrid (Spain) in order to understand which are the main drivers of its evolution. We interviewed 132 informants and analyzed the cultural importance and present-use of: 1) the Human food use-category compared with all the other use-categories, 2) the food plant species, 3) the Human food use-subcategories (e.g.,Vegetables, Fruits, Condiments or Beverages). The useful wild flora included 252 plant species, of which 74 were traditionally used as Human food, which is the most culturally important use-category. The most important species were three vegetables consumed cooked (Scolymus hispanicus, Bryonia dioica and Silene vulgaris), other two greens which were eaten raw (Rumex papillaris and Montia fontana), a condiment (Thymus zygis) and a fruit (Rubus ulmifolius). Among food use-categories, Vegetables was the category with a higher Cultural Importance Index, but Beverages and Condiments had the lowest cultural Erosion Rate. We found several drivers of change in the use of wild food plants, some enhancing the trend of abandonment that affects differently certain uses and species and others encouraging their maintenance. Factors that may explain the general erosion trend are linked to the abandonment of traditional agricultural practices and shepherding: 1) the decrease in the abundance and quality of wild food plants; 2) wild food plants are no longer necessary for subsistence; 3) the reduction of time spent in the countryside and 4) the negative connotations of some species that are considered famine food. On the other hand, there are several motivations for gathering and using wild food plants: 1) gathering is seen as a leisure and community building activity, 2) the intense flavor of wild plants, which cannot be substituted by cultivated or commercial ones, 3) positive values associated to some species consumed as everyday food that are now considered delicatessen and 4) the medicinal role of food, mainly food uses closer to medicine such as Beverages and Condiments.